A computer-based decision support system for knowledge management in the swine industry. (24th September 2021) - Trujillo-Díaz, Johanna; Herrera, Milton M.; Díaz-Piraquive, Flor Nancy
The swine industry contributes to food security around the world. However, the most vulnerable point in the industry occurs at the pig production cycle. This production cycle generates an unbalance between supply and demand, which affects profitability. This paper shows a computer-based decision support system for Knowledge Management (KM) which contributes to improving the profitability performance management into the swine industry. The computer-based system allows assessing decision alternatives on the dimensions of the KM capacity and profitability performance. This tool contributes to generating integration strategies for the swine industry - four simulation scenarios was designed for representing a pig company in the Colombian case.